Cost benefit snalysis of automation: an introduction to QuickBooks in Deligram Technology Ltd. - Mahabub, Aysha (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.